2016
DOI: 10.14260/jemds/2016/1175
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Mycological Profile of Onychomycosis in a Tertiary Care Centre of Tripura

Abstract: BACKGROUND AND OBJECTIVESOnychomycosis is an underreported progressive, recurrent fungal nail infection of human beings. So far, there is no documented study regarding causative agents of Onychomycosis in Tripura. In view of this, the study was conducted in a tertiary healthcare centre of Tripura aiming laboratory diagnosis of Onychomycosis with objectives of, (1) Epidemiology of Onychomycosis among the study subjects, (2) Profiling of aetiological agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…Among dermatophytes, Trichophyton mentagrophyte (19.96%) was the predominant species followed by T. rubrum (10.86%). The finding is similar to studies done by Bhatia et al [24] and Debbarma et al [25]. While in several other Indian studies, T. rubrum was elicited as the commonest dermatophyte [14,26].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among dermatophytes, Trichophyton mentagrophyte (19.96%) was the predominant species followed by T. rubrum (10.86%). The finding is similar to studies done by Bhatia et al [24] and Debbarma et al [25]. While in several other Indian studies, T. rubrum was elicited as the commonest dermatophyte [14,26].…”
Section: Discussionsupporting
confidence: 90%
“…Many other studies conducted in different parts of India and abroad have also reported dermatophytes as the commonest cause of onychomycosis [21,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%